Introduction to “Propeller Flaps” - Pignatti, Marco; Hallock, Geoffrey G. (Seminars in Plastic Surgery, 2020)
The editors of this issue of Seminars in Plastic Surgery dedicated to propeller flaps met in 2009 at the “1st Tokyo Meeting on Perforator and Propeller Flaps.” On that occasion, as part of the advisory panel of the meeting, they contributed to the definition and classification of these flaps. Since then, several evolutions and new applications of propeller flaps appeared in the literature. In 2019, the editors met again in Bologna, Italy, where they decided to collect the experiences from prominent authors in propeller flap surgery and provide them to the readers in this monographic dedicated publication.
Keywords: history of propeller flaps; monographic issue; propeller definition; propeller classification